Derivatisation of parthenolide to address chemoresistant chronic lymphocytic leukaemia. Issue 8 (1st August 2019) - Li, Xingjian; Payne, Daniel T.; Ampolu, Badarinath; Bland, Nicholas; Brown, Jane T.; Dutton, Mark J.; Fitton, Catherine A.; Gulliver, Abigail; Hale, Lee; Hamza, Daniel; Jones, Geraint; Lane, Rebecca; et al.
Abstract : A parthenolide-derivative with favourable pharmacokinetic properties and good activity against drug-resistant chronic lymphocytic leukaemia is reported. Abstract : Parthenolide is a natural product that exhibits anti-leukaemic activity, however, its clinical use is limited by its poor bioavailability. It may be extracted from feverfew and protocols for growing, extracting and derivatising it are reported . A novel parthenolide derivative with good bioavailability and pharmacological properties was identified through a screening cascade based on in vitro anti-leukaemic activity and calculated "drug-likeness" properties, in vitro and in vivo pharmacokinetics studies and hERG liability testing. In vitro studies showed the most promising derivative to have comparable anti-leukaemic activity to DMAPT, a previously described parthenolide derivative. The newly identified compound was shown to have pro-oxidant activity and in silico molecular docking studies indicate a prodrug mode of action. A synthesis scheme is presented for the production of amine7 used in the generation of5f .